Diagnostic and predictive value of inflammatory biomarkers on prior to prostate (Annals of Medical Research, 2023)
Aim: Prostate cancer (PCa) is the second most commonly diagnosed cancer in men. The cost-effectiveness of biomarkers assessed prior to the prostate biopsy is still a matter of debate. The present study aims to investigate the predictive role of inflammation markers that do not involve additional costs, before the first biopsy to increase the detection rates of clinically significant PCa and to avoid unnecessary biopsies.Materials and Methods: The present study was performed with a total of 236 patients who underwent prostate biopsy between January 2015 and December 2019 and who were selected by a random sampling method. The patients were divided into the two groups of benign (n = 140) and malignant (n = 96) based on the pathology results. Mann–Whitney U test and ROC analysis were used for the statistical analyses. A p value of 0.05).Conclusion: Inflammation biomarkers (NLR, PLR, and SII) assessed before prostate biopsy did not contribute to the predictive factors currently used in the prediction of biopsy results.